Increasing Sepsis Rates in the United States: Results From National Inpatient Sample, 2005 to 2014. (September 2020) - Rubens, Muni; Saxena, Anshul; Ramamoorthy, Venkataraghavan; Das, Sankalp; Khera, Rohan; Hong, Jonathan; Armaignac, Donna; Veledar, Emir; Nasir, Khurram; Gidel, Louis
Objectives: To examine the trends in hospitalization rates, mortality, and costs for sepsis during the years 2005 to 2014. Methods: This was a retrospective serial cross-sectional analysis of patients ≥18 years admitted for sepsis in National Inpatient Sample. Trends in sepsis hospitalizations were estimated, and age- and sex-adjusted rates were calculated for the years 2005 to 2014. Results: There were 541 694 sepsis admissions in 2005 and increased to 1 338 905 in 2014. Sepsis rates increased significantly from 1.2% to 2.7% during the years 2005 to 2014 (relative increase: 123.8%; P trend < .001). However, the relative increase changed by 105.8% ( P trend < .001) after adjusting for age and sex and maintained significance. Although total cost of hospitalization due to sepsis increased significantly from US$22.2 to US$38.1 billion ( P trend < .001), the mean hospitalization cost decreased significantly from US$46, 470 to US$29, 290 ( P trend < .001). Conclusions: Hospitalizations for sepsis increased during the years 2005 to 2014. Our study paradoxically found declining rates of in-hospital mortality, length of stay, and mean hospitalization cost for sepsis. These findings could be due to biases introduced by International Classification of Diseases, Ninth Revision, Clinical Modification coding rules and increased readmission rates or alternatively due to increased awareness and surveillance and changing disposition status. Standardized epidemiologic registries should be developed to overcome these biases.